Tissue plasminogen activator in left ventricular assist device-related intravascular hemolysis after failed augmented anticoagulation. Issue 11 (November 2022) - Kenneth Sims, Robert; Srour, Nina; El Nihum, Lamees I; Hannawi, Bashar; Araujo-Gutierrez, Raquel; Cruz-Solbes, Ana S; Trachtenberg, Barry H; Hussain, Imad; Kim, Ju H; Kassi, Mahwash; Graviss, Edward A; Nguyen, Duc T; et al.
Objectives: We sought to examine the efficacy and safety of adding fibrinogen-guided low-dose multi-day Alteplase™ tissue plasminogen activator (tPA) in the management of intravascular hemolysis (IVH) in patients with the HeartMate II (HM-II) continuous flow (CF) left ventricular assist device (LVAD) who failed to achieve IVH resolution with conventional augmented anticoagulation (AAC). Background: IVH in patients with LVAD is often treated with AAC, failing which pump exchange is considered. We hypothesized that a trial of low-dose tPA after failed AAC therapy could resolve IVH and prevent pump exchange in some patients. Methods: We performed a retrospective study of 31 HM-II CF LVAD patients admitted to our center from January 2015 to January 2020 for IVH management who received tPA following failed AAC. Primary 6-month outcomes included successful IVH resolution, unsuccessful IVH resolution requiring pump exchange, gastrointestinal bleeding, ischemic and hemorrhagic cerebrovascular accident (CVA), and death. Results: Thirty-one patients with IVH were treated with tPA following failed AAC. Successful resolution of IVH occurred in 22/31 (71%) patients. Pump exchange occurred in 9/31 (29%) patients. Gastrointestinal bleeding occurred in 7/31 (22.6%) patients. Ischemic CVA occurred in 6/31 (19.4%) patients. Conclusions: Management of IVH with administration of low-dose tPA after failed AAC is feasible and may prevent pump exchange in some patients.